Clinical value of cytology in pleural effusions versus histology by medical thoracoscopy - Canessa, Pier Aldo; Manta, Carmen; Sivori, Massimiliano; Intersimone, Donatella; Fedeli, Franco (Rassegna di Patologia dell'Apparato Respiratorio, 2015)
Background. Pleural effusions are frequently the presenting symptom of neoplastic disease. The cytological examination of pleural effusion is recognized as being the most commonly used investigation in the diagnosis of malignancy.Objectives. The aim of this study was to assess the sensitivity and specificity of cytology in pleural exudate effusions compared to the histology obtained by medical thoracoscopy as the diagnostic gold standard examination.Methods. We assessed 256 consecutive thoracoscopies performed between 2006 and 2010 in the Pneumology ward of the Sarzana Hospital (Italy). Pleural disease was diagnosed based on histological criteria.Results. We had 80 mesotheliomas, 52 pleural metastasis and 124 non malignant pleural diseases. Cytologic examination permitted the diagnosis of 35 mesotheliomas (28 epithelioid, 2 sarcomatoid, 2 desmoplastic, 3 biphasic), 37 pleural metastasis (21 lung, 8 breast, 1 lymphoma, 3 ovary, 1 stomach, 1 liver, 2 uterus). Cytology remained negative in 45 mesotheliomas (28 epithelioid, 11 sarcomatoid, 2 desmoplastic, 4 biphasic) and in 15 pleural metastasis (6 lung, 4 breast, 3 lymphoma, 1 sarcoma, 1 thyme). The sensitivity of cytology was 53.8% and the specificity was 97.6%; the sensitivity of pleural metastasis was greater than the sensitivity of malignant mesothelioma (71.2% vs 43.7%).Conclusions. We conclude that sensitivity of first cytology samples in pleural effusion remains about 50% in the immunocytochemical era and that it is too low to avoid a diagnostic thoracoscopy. A negative cytologic examination of pleural effusion does not exclude a diagnostic thoracoscopy; a positive cytology for metastasis could exclude diagnostic thoracoscopy, even though thoracoscopy might be performed for talc poudrage. A positive cytology for mesothelioma requires confirmation by histology obtained by thoracoscopy.